Prognostic factors of overall and prostate‐specific antigen‐progression‐free survival in metastatic castration‐resistant prostate cancer patients treated with 177Lu‐PSMA‐617. A single‐center prospective observational study. Issue 8 (15th March 2023) - Telli, Tugce; Tuncel, Murat; Karabulut, Erdem; Aksoy, Sercan; Erman, Mustafa; Akdogan, Bulent; Caglar, Meltem
Abstract: Background: Metastatic castration‐resistant prostate cancer (mCRPC) is characterized by heterogeneity among patients as well as therapy responses due to diverse genetic, epigenetic differences, and resistance mechanisms. At this stage of the disease, therapy modalities should be individualized in light of the patients' clinical state, symptoms, and genetic characteristics. In this prospective study, we aimed to evaluate the outcome of patients with mCRPC treated with 177 Lutetium labeled PSMA‐617 therapy (PSMA‐RLT), as well as baseline and therapy‐related parameters associated with survival. Methods: This prospective study included 52 patients who received two to six cycles of PSMA‐RLT. Primary endpoints were overall survival (OS) and prostate‐specific antigen (PSA)‐progression‐free survival (PFS). 18 F‐Fluorodeoxyglucose (FDG) and 68 Ga‐PSMA (PSMA) Positron Emission Tomography/Computer Tomography (PET/CT) scans were performed for a comprehensive assessment of tumor burden and heterogeneity. Biochemical, imaging, clinical, and therapy‐related parameters were analyzed with the Kaplan–Meier, log‐rank, and Cox regression analyses to predict OS and PFS. Results: Median OS and PSA‐PFS were 17.7 (95% confidence interval [CI]: 15.2–20.2) and 6.6 months (95% CI: 4.5–8.8), respectively. Primary resistance to PSMA‐RLT (hazard ratio [HR]: 12.57, 95% CI: 2.4–65.2, p : 0.003), <30% PSA response rate after first cycle of PSMA‐RLT (HR: 1.016, 95% CI: 1.006–1.03, p : 0.003), FDG > PSMA disease (HR: 4.9, 95% CI: 1.19–20.62, p : 0.03), PSA doubling time (PSA DT) of ≤2.4 months (HR: 15.7, 95% CI: 3.7–66.4, p : <0.0001), and low hemoglobin levels (HR: 0.59, 95% CI: 0.41–0.83, p : 0.003) were correlated with poor OS in the multivariate analysis. Bone scintigraphy >  PSMA disease (HR: 5.6; 95% CI: 1.8–17, p : 0.002) and high C‐reactive protein (HR: 1.4, 95% CI: 1.1–1.7, p : 0.001) were significant predictive biomarkers for PFS in the multivariate analysis. Conclusion: PSA response rate and pattern to PSMA‐RLT are the most important predictors of survival in patients receiving PSMA‐RLT. Being a strong predictive biomarker, combined FDG and PSMA PET can be helpful for the decision of PSMA‐RLT eligibility.